Desenvolvimento de uma ferramenta para análise do estudo de impacto de vizinhança na área de emissões sonoras - Alves, Alessandro (2013)
I n order to provide effective control regarding neighborhood impacts, a town needs well-defined and clear laws and methods of assessment. The federal law known as the City Statute established the Neighborhood Impact Study (NIS). The document states that its development should follow minimum criteria to ensure quality in the environment where the study becomes necessary and that towns should legislate on the NIS to define which projects should be presented as a condition for its approval. Since the publication of the Law of Use and Occupation in 2009 to date, the specific laws, made at the municipal level in Santa Maria-RS, do not help the public agency to have an effective means of collecting and evaluating studies. Neither there is a definition of minimum items to be evaluated, whether in EIVs for new enterprises or establishments already set, which must be submitted with the technical reports evaluating the sound pressure level produced. The following research aims to develop a tool for analysis of NIS, to be used by municipal authorities in order to standardize the method of assessing these studies specifically in the area of noise. The research is characterized as applied to the nature and the objectives as exploratory. It brings a qualitative and quantitative approach taking into account many factors, like the items required in an NIS to secure the deployment of a project, without that entail damage to its surroundings. It also allows the evaluation of existing laws ruling the development of NISs. The technical procedure used was the case study, with data collection in the city of Santa Maria-RS, where with the help of the technical staff of the Office of the city was recorded a total of 108 NISs for 3 months, for a thorough detailing of the research. Still, as seen in both the identification of laws related to NISs as the data collection performed with the assistance of the Office of the city, were assessed deficiencies of these laws, where NISs, specifically for this work-related noise emissions, are not delimited their minimum items so difficult for the evaluation team and for the professionals responsible for their preparation either. Thus propose modifications of the laws to fill the gaps in them, addition to delimiting minimum items through a tool for analysis of NISs in the area of noise. This way it is expected to contribute not only to the quality and agility of NISs, but also achieve all objectives.